Taxonomic position and glochidia from the freshwater mussel, Anodonta luteola (Unionoida: Unionidae), in Costa Rica (UNED Research Journal, 2017)
Glochidia larvae from Anodonta luteola were observed in gills of Oreochromis niloticus from a farm in Cañas, Guanacaste. Samples  were taken and analyzed by electron microscopy (SEM) and light microscopy. Glochidia were 311, 8μm total length (TL), 331,7μm totalheight (TH), and 251,1μm hinge dorsal length (HDL). Anodonta has 21species reported for the Panamica province, and A. luteola has five synonyms, often used in different reports.
Keywords: Anodonta luteola; taxonomic position; glochidium morphology; Costa Rica